2021
DOI: 10.1155/2021/7552510
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Physiological Index Monitoring of Wearable Sports Training Based on a Wireless Sensor Network

Abstract: According to the development needs of wireless sensor networks, this paper uses the combination of embedded system and wireless sensor network technology to design a network node platform. This platform is equipped with a sports training sensor module to measure the physiological indicators of the ward in real time. The network node sends the collected physiological parameters to a remote monitoring center in real time. First, according to the generation mechanism of the physiological index signal and the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the "Sports Science and Technology" program of the State General Administration of Sport, the scientific monitoring and research of sports training as a primary issue, and based on this has established six key laboratories of training monitoring, sports psychology, sports trauma, and medical supervision, sports nutrition, information research, physical training and recovery [8][9]. Each ball management center also attaches great importance to all levels of the national team's physiological function assessment biochemical index testing in large-scale tournaments specifically equipped with scientific and technological research teams to assist the coaching staff in determining the content of the training, arrangement of the training load, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the "Sports Science and Technology" program of the State General Administration of Sport, the scientific monitoring and research of sports training as a primary issue, and based on this has established six key laboratories of training monitoring, sports psychology, sports trauma, and medical supervision, sports nutrition, information research, physical training and recovery [8][9]. Each ball management center also attaches great importance to all levels of the national team's physiological function assessment biochemical index testing in large-scale tournaments specifically equipped with scientific and technological research teams to assist the coaching staff in determining the content of the training, arrangement of the training load, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Et al. Designed a network node platform by combining an embedded system and wireless sensor network technology, equipped with sensors for sports training to measure the physiological indexes of sports training, and simulation experiments were conducted to confirm the reliability of the motion measurement function of the platform system [19]. Zhao, S. Et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lu, Z. et al applied an embedded system combined with wireless sensor network technology to design a network node platform. Equipped with sensors for sports training to measure the physiological index information of sports training, simulation experiments to confirm the reliability of the movement measurement function of the platform system [19]. Zhao, S. et al studied the role and significance of scientific support system training for colleges and universities via competitive sports, carried out tracking surveys and in-depth analyses of diving athletes using scientific training, and found that science and technology and system theory-based training is beneficial to the cultivation of high-level college athletes in general colleges and universities [20].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%